2017
DOI: 10.1177/0003489417716186
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell–Mediated Paracrine Signaling Alters Fibroplasia in Human Vocal Fold Fibroblasts in Vitro

Abstract: Conditioned media affected many profibrotic cell activities in TGF-β1-stimulated VFFs, likely related to altered TGF-β signaling. These data provide preliminary insight regarding the antifibrotic effects of MSCs and further support their progression to clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…hAECs, which can be obtained from the discarded amnion tissue via noninvasive procedure, have emerged as an alternative resource for stem cell therapy [ 22 ]. It was reported that the reparative effect of stem cells was mediated by paracrine signaling with the release of biologically active molecules affecting cell migration and/or proliferation [ 23 ]. In particular, the exosomes, an essential paracrine factor secreted by many cell types, played a dominant role in the regulation of tissue repair and regeneration [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…hAECs, which can be obtained from the discarded amnion tissue via noninvasive procedure, have emerged as an alternative resource for stem cell therapy [ 22 ]. It was reported that the reparative effect of stem cells was mediated by paracrine signaling with the release of biologically active molecules affecting cell migration and/or proliferation [ 23 ]. In particular, the exosomes, an essential paracrine factor secreted by many cell types, played a dominant role in the regulation of tissue repair and regeneration [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hiwatashi et al . () demonstrated in vitro the inhibiting effects of the medium in which bone marrow‐derived MSC were cultured on the secretion of transforming growth factor‐β1 by human vocal fold fibroblasts. In the experiments in vivo , 1 month postimplantation the overwhelming majority of the vocal fold‐implanted MSC were proven dead, no long‐term engraftment was observed, that also indicated the realisation of the stem cell regenerative potential via paracrine mechanisms (Hertegård et al ., ; Bartlett et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the review (Vizoso et al, 2017), the secreted wide spectrum of anti-inflammatory mediators and cytokines, as well as different growth factors, has a greater significance in wound healing than direct proliferation of stem cells at the site of their implantation. Hiwatashi et al (2017) demonstrated in vitro the inhibiting effects of the medium in which bone marrow-derived MSC were cultured on the secretion of transforming growth factor-β1 by human vocal fold fibroblasts. In the experiments in vivo, 1 month postimplantation the overwhelming majority of the vocal fold-implanted MSC were proven dead, no long-term engraftment was observed, that also indicated the realisation of the stem cell regenerative potential via paracrine mechanisms (Hertegård et al, 2006;Bartlett et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human amnion mesenchymal stem cells (hAMSCs) are obtained by surgery from human amniotic tissue and are now often used as an alternative resource for stem cell therapy [13]. According to research reports, stem cells exert repair effects through paracrine signaling and affect cell proliferation and migration through the release of bioactive factors [14]. Exosomes are important paracrine factors secreted by numerous cell types, and current studies have found that they play a dominant role in tissue repair and regeneration [15].…”
Section: Discussionmentioning
confidence: 99%